The RELATIONSHIP OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE PT. AKA SINAR GROUP JAKARTA PUSAT - Siahaan, Sincha; Sihombing, Christina N. .; Tarigan, Lukas (Universitas Kristen Indonesia, 2018)
The purpose of this study is to see the relationship between leadership style and organizational culture, the relationship between leadership and employee performance at PT. AKA Sinar group data collection was carried out through the distribution of questionnaires. This study had a sample of 20 employees and the data were analyzed using Spearman rank correlation analysis using SPSS Version 20. Research can show that (1) seeing the relationship between leadership style and organizational culture with employee performance at PT. AKA Sinar group. With Rank Spearman analysis obtained correlation value of 0.556 with a significance of 0.011 < 0.05, positive value and thre is a moderate relatinship. (2) There is an relationship with employee performance at PT. AKA Sinar group obtained spearman rank correlation coefficient of (0.455) and the significance of 0.44 < 0.05, with these results can be taken a decision that is positive and there is a moderate relationship. Keyword: organizational culture, leadership, employee performance